Benthic Macroinvertebrates as Ecological Indicators: Their Sensitivity to the Water Quality and Human Disturbances in a Tropical River - Tampo, Lallébila; Kaboré, Idrissa; Alhassan, Elliot H.; Ouéda, Adama; Bawa, Limam M.; Djaneye-Boundjou, Gbandi (Frontiers in Water, 2021)
Macroinvertebrate metrics are helpful tools for the assessment of water quality and overall aquatic ecosystem health. However, their degree of sensitivity and the most reliable metrics for the bioassessment program development are very poorly studied in Togo. This study aimed to test the sensitivity of metrics calculated at the family and genus levels. A total of 21 water quality parameters and macroinvertebrates' data were collected during three periods at 20 sampling sites within the Zio River. The canonical correspondence analysis (CCA), factor analysis (FA), and Spearman's correlation analysis were conducted on water quality parameters and macroinvertebrates' data. The results reveal that macroinvertebrate structure and composition were affected by water quality parameters related to human disturbances. In this study, three groups of macroinvertebrate communities were identified including sensitive taxa such as Ephemeroptera, Plecoptera, Trichoptera, and Odonata (EPTO) taxa; the resistant or resilient taxa such as Oligochaeta, Hirudinea, Diptera, and Pulmonates (OHDP) taxa; and tolerant taxa such as Prosobranchia, Bivalvia, Lepidoptera, Heteroptera, and Coleoptera (PBLHC). All the 13 macroinvertebrate-based metrics were found to be sensitive in the detection of water quality and human disturbance gradients. However, metrics related to EPTO and the tolerance measure [multimetric index of the Zio River basin (MMIZB), Average Score per Taxon (ASPT), and Biological Monitoring Working Party (BMWP)] are the most robust in discrimination of pressure gradients. This study reveals that macroinvertebrates are sensitive and can be used for the bioassessment program development at the order, family, or genera taxonomic level.